Reconciled diversity response to John Armstrong - DeBorst, Ruth Padilla (Missiology, 2026)
Beyond bridging church traditions, the urgent challenge is reconciling diversity across ethnic lines and advocating for the rights of minoritized and persecuted ethnic communities in the United States today.